The place behind the case: leptospirosis risks and associated environmental conditions in a flood-related outbreak in Rio de Janeiro - Barcellos Christovam; Sabroza Paulo Chagastelles (Cadernos de Saúde Pública, 2001)
The environmental context in which a leptospirosis outbreak took place during the summer of 1996 in the Rio de Janeiro Western Region was examined by using spatial analysis of leptospirosis cases merged with socio-demographic data using Geographic Information System (GIS). Risk areas were mapped based on flood and solid waste accumulation information for the region. Incidence rates were calculated for each area by the division of number of cases per total population in the specific areas. Higher rates were observed for census tracts inside the flood risk area and in the vicinities of waste accumulation sites. These findings are in agreement with the expected risk of leptospirosis, evidencing the role of environmental and collective factors in the determination of the disease.